Financování podnikatelských aktivit - Maleček, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Tato bakalářská práce je zaměřena na financování podnikatelských aktivit konktrétně na financování dlouhodobého majetku, osobního automobilu pro dodavatelskou firmu. Teoretická část práce je zaměřena na odbornou literární rešerši a vysvětlení základních pojmů. V analytické části jsou provedeny strategické a finanční analýza konkrétní firmy. Návrhová část je zaměřena na představení konkrétního předmětu financování a následnému návrhu nejvhodnějšího způsobu financování.

This bachelor thesis is focused on the financing of business activities, specifically on the financing of fixed assets, a car for a supplier company. The theoretical part of the work is focused on professional literature search and explanation of basic concepts. In the analytical part, strategic and financial analysis of a specific company is performed. The practical part is focused on the introduction of a specific subject of financing and the subsequent proposal of its most suitable method of financing.
Financing of Business Activities
Keywords: financování; dlouhodobý majetek; zdroje financování; PEST; SWOT; úvěr; leasing; financing; fixed assets; sources of financing; PEST; SWOT; loan; leasing